The Profile of Laryngopharyngeal Reflux Patients at Dr. Soetomo Teaching Hospital, Surabaya Indonesia - Ami Pratami Munifah1 , Rizka Fathoni Perdana1 , Sri Herawati Juniati1, Muhtarum Yusuf1 , Erni Rosita (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Laryngopharyngeal reflux (LPR) is a collection of symptoms due to gastric contents orgastroduodenal backflow reflux fluid. The prevalence of LPR is very difficult to determine because of thelimitations of the gold standard and the considerable variation in LPR symptoms.Aim: to determine the profile of laryngopharyngeal reflection patientsMethod: This research used analytic retrospectively, the data obtained from the medical record of outpatientunit of the Otolaryngology-Head and Neck Surgery Outpatient Unit, Dr. Soetomo Teaching Hospital. Thedata obtained in the study are displayed in tables and analyzed descriptively. The research sample was takenaccording total sampling from January 2017 to December 2018 who met the inclusion criteria.Result: 42 samples met the requirements. 64.29% patient were female and 35.71% were male with themajority of patient was patient was 41-50 years old (26.19%). Most of the comorbidities had a history ofGERD about 76.2%. The mean of the reflux symptom index score performed was 18.38, with a standarddeviation of ± 8.01 and the reflux findings scores was 9.11, with a standard deviation of ± 4.25. The mostfrequent complaints experience was frequent mucus or clearing of the throat (90.48%) and the most frequentfinding in laryngeal endoscopy was erythema/hyperemia (88.1%).Conclusion: Profiles of patients with laryngopharyngeal reflux were mostly female with age between 41and 50 years old. The main complaint of the throat felt blocked, and the most comorbidities were GERD.